Effect of Vachellia tortilis Leaf Meal and Sunflower Oil Inclusion in Supplementary Diets of Lambs on In Vitro Short-Chain Fatty Acid and Gas Production and In Vivo Growth Performance - Mahlogonolo Daniel Serumula; Bulelani Nangamso Pepeta; Mehluli Moyo; Terence Nkwanwir Suinyuy; Ignatius Verla Nsahlai (Animals)
This study examined the effect of dietary Vachellia tortilis leaf meal and sunflower oil inclusion in supplementary diets on in vitro short-chain fatty acid (SCFA) and gas production and the in vivo growth performance of lambs. Four concentrate dietary treatments comprising control (CL), Vachellia tortilis leaf meal (VT), sunflower oil (SFO), and Vachellia tortilis leaf meal sunflower oil (VSFO) were formulated. Eight Merino lambs were blocked into two live weight blocks where animals within each block were randomly assigned to dietary treatments, making two animals per treatment. Lambs were offered a concentrate diet of 480 g/day per head, with urea-treated hay fed as a basal diet. Dietary effects were evaluated for in vitro short-chain fatty acid and gas production and 28-day growth performance of lambs over three study periods. The inclusion of VT and SFO showed no statistically significant effect on total SCFAs, acetate to propionate (A:P) ratio, methane (CH4), and carbon dioxide (CO2) production (p > 0.05), which might be attributable to low experimental units. The hourly A:P ratio and CH4 yield were the highest (p < 0.05) at 16 h of incubation. The inclusion of VT showed no statistically significant effect on growth performance and gas production due to the small sample size. Therefore, VT can be explored as a supplementary protein source in lamb diets given the impression of not showing any causative adverse effects on growth performance and in vitro gas production, although further research with larger sample sizes is needed to confirm these findings.